Penghitungan Efektivitas Pemberdayaan Desa Menggunakan Indeks Desa Zakat (IDZ) (Studi Kasus : Desa Laharpang Kediri) - Novitasari Novitasari; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aimed to identify and assess the effectivity of village empowerment using Zakat Village Index (IDZ). This empowermentanalyzed included five main dimensions, which are economy, health, education, social communiy, and da’wah. This research result based on IDZ Score Range. This research used descriptive-quantitative method with case study. The object of the research was Laharpang Village—Desa Laharpang, Kabupaten Kediri. It also used interview based on questionnaire, observation, and documentation. Then, the result of the research was analyzed by based on the procedure of IDZ to get result and conclusion. The result of the research showed that the calculation of Zakat Village Index indicated the excellent village quality and create effective empowerment using zakat with IDZ score 0,896 that means very good and effective.Keywords: Effectivity, Village Empowerment, Zakat, Zakat Village Index (IDZ)